Common Fixed Point of the Commutative F-Contraction Self-Mappings with Uniquely Bounded Sequence (Journal of Nonlinear Modeling and Analysis, 2025)
We establish the existence of a common fixed point for mappingsthat satisfy and extend the F-contraction condition. To support our findings,we present pertinent definitions and properties associated with F-contractionmappings. Additionally, we establish an analogue to the Banach contractiontheorem. Our results contribute to the broader understanding of this field byextending and generalizing existing findings in the literature.
Keywords: Contraction mapping; fixed point; common fixed point.